Identity Politics and Social Fragmentation: A Comparative Study of Indonesia's 2024 Presidential Candidate Campaign Narratives - Muhamad Zaenal Asikin (Politeknik Siber Cerdika Internasional, 2025)
The 2024 Indonesian presidential election takes place in an increasingly complex socio-political atmosphere, characterized by the strengthening of identity politics and social fragmentation in the public sphere. Campaign narratives of presidential candidates play a strategic role in shaping public perceptions, building a support base, while paradoxically deepening the polarization of society. This phenomenon raises questions about how identity narratives are constructed and distributed in contemporary political campaigns. This study aims to compare the campaign narratives of three pairs of presidential and vice presidential candidates in the 2024 presidential election, focusing on identity issues (religion, ethnicity, social class) and their impact on social fragmentation. This research uses a qualitative approach with Fairclough's critical discourse analysis (AWK) model, as well as triangulation with social media data, official speeches, and campaign team statements. The results showed that the three candidate pairs used different narrative strategies in framing national identity, but simultaneously strengthened social segmentation based on political affiliation, religious symbols, and constructions of morality. Inclusive narratives were often overshadowed by populist rhetoric and